Combination of Ru(ii) complexes and light: new frontiers in cancer therapy. Issue 5 (20th May 2015) - Mari, Cristina; Pierroz, Vanessa; Ferrari, Stefano; Gasser, Gilles
<x xml:space="preserve">Abstract</x> In this perspective article, we present the recent achievements in the application of ruthenium complexes as photosensitizers and as photoactivatable prodrugs.